Komitmen Organisasi Dan Intention To Quit Karyawan Perbankan Syariah - Mujahid Quraisy; Mukhaer Pakkanna (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2015)
This study intends to explore the issue of employees’voluntary turnover at the stage of intention to quit, by testing the effect of the variables of psychological determinants (labor relations), i.e. organizational commitment, social commitment, religious commitment, and spiritual well-being as variables that allegedly can affect the intention to quit. Based on the differencece test of t-test, the findings of the study include five things. First, there was significant difference in the intention to quit of human resources in Islamic banks and non-Islamic banks. The average of the intention to quit of Islamic banks human resources was lower than that of the non-Islamic banks. Secondly, there was no significant difference between the organizational commitment of the human resources of Islamic banks and non-Islamic banks. Third, there was significant difference in the social commitment of the human resources of Islamic banks and non-Islamic banks. The average of the social commitment of the human resources of Islamic banks was higher than that of the non-Islamic banks. Fourth, there was significant difference in the religious commitment of the human resources of Islamic banks and non-Islamic banks. Fifth, there was significant difference in the spiritual well-being of the human resources of Islamic banks and non-Islamic banks.